A Brief Analysis of the Shadow Economy in Europe - Loredana Maftei (CES Working Papers, 2013)
Shadow economy affects all country around the world. European countries are affected by undeclared work, under-reporting and tax evasion. This phenomenon increases from West to East, the most affected being the Balkan area. The size of shadow economy is growing due to government actions, such as regulation and tax implementation. From a macroeconomic perspective, the economic cycle sustain the shadow economy levels. To combat this phenomenon it is necessary to adopt electronic payments, to reduce tax implementations and social contributions, to bring encouragement in cash deposits use and broaden credit cards.
Keywords: O17; O5; E26; 330; shadow economy; tax evasion; regulation; undeclared work; under-reporting Romania